Digital trust as an institutional capability for SME internationalization: A grounded theory from Indonesia - Wardha Nilawati; Sudarmiatin Sudarmiatin; Heri Pratikto (Jurnal Inovasi Ekonomi, 2026)
The platform economy has transformed how small and medium-sized enterprises (SMEs) participate in international markets by reducing traditional barriers to cross-border trade. However, successful digital internationalization remains uneven among SMEs in emerging economies, suggesting that platform participation alone is insufficient to achieve international competitiveness. This study develops a substantive theory explaining how SMEs build digital trust as an institutional capability that supports internationalization within platform economy ecosystems. Adopting a Constructivist Grounded Theory approach, the study collected data from 25 SME owners in Banyuwangi, Indonesia, through theoretical sampling, semi-structured in-depth interviews, participant observation, and document analysis. Data were analyzed iteratively using initial, focused, and selective coding supported by NVivo. The findings identify Layered Digital Trust Building as the core category explaining how SMEs progressively accumulate trust through product presentation, authentic local narratives, service responsiveness, and reputation management across digital touchpoints. These findings are integrated into the Digital Trust Escalation Model, which describes four sequential stages of capability development: Digital Presence, Social Proof, Authentic Narrative, and Brand Independence. The study demonstrates that platform economy primarily functions as an institutional infrastructure, whereas successful internationalization depends on SMEs' ability to transform platform participation into adaptive digital capabilities and institutional trust. Theoretically, the study extends the literature on platform economy and SME internationalization by conceptualizing digital trust as an institutional capability rather than merely a marketing outcome. The findings also provide practical implications for strengthening innovation ecosystems, capability development, and policy support to enhance SME competitiveness in emerging markets.